Diagnosis and Management of Articular Cartilage and Meniscus Pathology in the Posterior Cruciate Ligament-Injured Knee - Ewing, Michael A.; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2021)
Posterior cruciate ligament (PCL) injuries commonly occur in association with participation in sporting or recreational activities or due to a direct trauma. Cartilage and meniscal lesions are prevalent in PCL-injured knees with increasing likelihood and severity based on extent and duration of trauma to the knee. As such, comprehensive diagnostics should be performed to ascertain all related pathology, and patients should be thoroughly educated regarding treatment options, likely sequelae including posttraumatic osteoarthritis, and associated outcomes. Treatments should address the joint as an organ, ensuring stability, alignment, and functional tissue restoration are optimized by the most efficient and effective means possible. Compliance with patient- and procedure-specific postoperative management protocols is critical for optimizing successful outcomes for these complex cases. The objectives of this review article are to highlight the likelihood and importance of osteochondral and meniscal pathology in the PCL-injured knee, and to provide the best current evidence regarding comprehensive evaluation and management for PCL-injured knees with cartilage and/or meniscal comorbidities.
Keywords: posterior cruciate ligament injuries; cartilage; meniscal lesions; comprehensive evaluation; complex knee injury treatment